Unima risk management development - Sumual, Herry; Sumilat, Juliana Margareta (Technium Social Sciences Journal, 2022)
This study aims to develop a risk management map at Manado State University. This research uses development research with 4D model which stands for Define, Design, Development and Dissemination. Educational organizations such as Unima are organizations that have activities in which they must face situations with uncertainty factors that manifest in the form of opportunities and threats in an effort to achieve Unima's vision and mission itself. The threats and opportunities that manifest are risks that must be faced and managed to help Unima achieve its vision and mission. In an effort to achieve Unima's vision and mission, it is necessary to carry out risk management activities carried out by the risk management unit. Therefore, Unima needs to present a unit that is responsible for managing and managing risks, which of course always communicates and coordinates with related leaders